Virtual reality as a versatile tool for research, dissemination and mediation in the humanities - Paul François; Jeffrey Leichman; Florent Laroche; Françoise Rubellin (Virtual Archaeology Review)
The VESPACE project aims to revive an evening of theatre at the Foire Saint-Germain in Paris in the 18th century, by recreating spaces, atmospheres and theatrical entertainment in virtual reality. The venues of this fair have disappeared without leaving any archaeological traces, so their digital reconstruction requires the use of many different sources, including the expertise of historians, historians of theatre and literature. In this article, we present how we have used video game creation tools to enable the use of virtual reality in three key stages of research in the human sciences and particularly in history or archaeology: preliminary research, scientific dissemination and mediation with the general public. In particular, we detail the methodology used to design a three-dimensional (3D) model that is suitable for both research and virtual reality visualization, meets the standards of scientific work regarding precision and accuracy, and the requirements of a real-time display. This model becomes an environment in which experts can be immersed within their fields of research and expertise, and thus extract knowledge reinforcing the model created –through comments, serendipity and new perspectives– while enabling a multidisciplinary workflow. We also present our tool for annotating and consulting sources, relationships and hypotheses in immersion, called PROUVÉ. This tool is designed to make the virtual reality experience go beyond a simple image and to convey scientific information and theories in the same way an article or a monograph does. Finally, this article offers preliminary feedback on the use of our solutions with three target audiences: the researchers from our team, the broader theatre expert community and the general public. Highlights: